Analysis on the Governance Wealth of Republic of Indonesia Police Primary Cooperative of Magetan Resort in 2011-2015 - Prasetio, Vensia Adzania (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to  reveal the governance of Republic of Indonesia Police  Primary  Cooperative,  Magetan  Resort (Primkopol  Polres  Magetan)  in 2011-2015 based on the Decree of Small Business and Cooperatives Minister of Indonesia Republic No. 14/Per/M.KUKM/XII/2009 comprising capital aspects, productive assets quality,  management,  efficiency, liquidity,  self-reliance,  and self-identity of cooperative.This is a descriptive quantitative research focusing on a case study at Primkopol  Polres  Magetan  in  2011-2015.  The  data analysis  was  run  by comparing the calculation result on the health level aspects based on the Decree of Small    Business   and     Cooperatives     Minister    of    Indonesia    Republic No. 14/Per/M.KUKM/XII/2009.The result indicates that the health level of Primkopol Polres Magetan in 2011-2015 was quite healthy as the average score was 77.29. The score detail is as follow: (1) capital aspect average score was 15.00 categorized as healthy level; (2) productive asset quality aspect reached 23.70 average score which was categorized as healthy level; (3) management aspect attained average score of 12.96 categorized as healthy level; (4) efficiency aspect demonstrated an average score of 7.00  categorized  as quite  healthy level; (5)  liquidity got  6.75 as its average score which was categorized as unhealthy level; (6) self-reliance and cooperative growth aspects demonstrated an average score of 6.40 categorized as quite healthy level; and (7) self-identity cooperative aspect reached 5.75 as its average score which was categorized as quite healthy level. Among the seven assessment  items,  capital  and  productive  asset quality  aspects  were  the  best aspects compared to liquidity and cooperative self-identity aspects.Keywords: Health Level, Capital Aspect, Productive Asset Quality Aspect, Management Aspect, Efficiency Aspect, Self-Reliance and Cooperative Growth Aspect, and Self-Identity Aspect.